Analisis Persepsi Masyarakat Non Muslim terhadap Produk Asuransi Syariah di PT Allianz Batu Bara - Eka Aprila Pratiwi; Yusrizal Yusrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
ABSTRACT         The development of sharia insurance in Indonesia is quite positive and has many enthusiasts because the majority of Indonesia's population are Muslims. Sharia insurance is an attempt to protect and help each other between insurance participants. The return pattern for dealing with risks in sharia insurance uses a contract (contract) system in accordance with Islamic law. The increasing development of sharia insurance in Indonesia has occurred very rapidly since 2011. This development is evident from the emergence of various insurance companies that have begun to offer insurance products based on Islamic principles. Until now, the trend of sharia insurance is still increasing. Based on AASI research, it was found that the gross contribution of Islamic insurance in Indonesia reached IDR 11.55 trillion, where there was an increase of 51.89% year on year as of June 2021. This research aims to meet the perceptions of the non-Muslim community towards Islamic insurance products in PT. Allianz Batu Bara and look at the role of non-Muslim communities in sharia insurance products. This research uses qualitative research with a descriptive approach. Data collection techniques in this study are observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and verification. Based on research conducted at PT Alliaz Batu Bara, it shows that non-Muslim people's perceptions of Islamic insurance products can vary depending on their knowledge, experience, and understanding of Islamic insurance principles.Keywords: perceptions of non-Muslims, sharia insurance products